2010
DOI: 10.1007/s11886-009-0080-2
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Women: Disparities and Outcomes

Abstract: Stroke is the leading cause of disability in the United States and affects 15 million people worldwide. Studies performed in various parts of the world have found differences between sexes in stroke incidence, prevalence, mortality, and outcomes. Although men are at higher risk of stroke for most age groups below age 85 years, after this age the incidence reverses dramatically, with women being much more at risk. Furthermore, recent studies suggest that women have worse recovery than men post-stroke. Many aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
144
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(159 citation statements)
references
References 53 publications
1
144
2
4
Order By: Relevance
“…OVX mice are frequently used as a model of post-menopausal women whom remain at higher risk of stroke and poor outcomes [5]. We reported that non-OVX young females are comparatively resistant to embolic stroke injury, which is lost after ovariectomy [10].…”
Section: Introductionmentioning
confidence: 99%
“…OVX mice are frequently used as a model of post-menopausal women whom remain at higher risk of stroke and poor outcomes [5]. We reported that non-OVX young females are comparatively resistant to embolic stroke injury, which is lost after ovariectomy [10].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 5.5 million die (including 3 million women and 2.5 million men) and another 5 million are left permanently disabled, placing a burden on family and community (Mackay and Mensah 2004). Women differ from men in stroke symptoms, subtypes, and risk factors (Beal 2010;Persky et al 2010;Wassertheil-Smoller 2010). In addition to common cardiovascular risk factors, for instance, hypertension and hyperlipidemia, women are confronted with such unique risk factors as oral contraceptive use.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of multiple sclerosis is greater in women [6] , who, however, show a more benign course of the disease [7] . Differences between sexes in stroke incidence, prevalence, mortality and outcomes are also well known [8] .…”
Section: Introductionmentioning
confidence: 99%